Spatial Durbin Model (SDM) For Identified Influence Dengue Hemorrhagic Fever Factors in Kabupaten Malang - Suri, Indah Resti Ayuni; Henny, Pramoedyo; Handamari, Endang Wahyu (CAUCHY, 2012)
Dengue Hemorrhagic Fever or usually populer call DBD (Demam Berdarah Degue) is the cronic desease that caused by virus infection who carry by Aedes Aegypti mousquito. The observation act by DBD descriptioning and some factors territorial view that influence them, also DBD’s modeling use Spatial Durbin Model (SDM). SDM is the particullary case from Spatial Autoregresive Model (SAR), it means modeling with spatial lag at dependen variable and independen variable. This observation use ratio DBD invectors amount with population amount of citizenry at Kabupaten Malang in 2009. Some variable was used, those are the precentation of existention free number embrio, ratio of civil amount between family, procentation of healthy clinic between invectors and procentase of the invectors who taking care by medical help with amount of invectors. The fourth variables are independen variable to ratio of DBD invector amount with population of citizenry amount, as dependen variable trough spatial SDM modelling. The result of SDM parameter modelling, the significant influence variable in session % is the procentation of free amount embrio existention from their own district, the procentation of healthy clinic amount with the DBD invector amount from their own district, the ratio of the population of citizenry with the family from their neighborhood district, and the procentation of healthy clinic amount with the DBD invector amount from their neighborhood district.